COMMON CAUSES OF CHILD MORTALITY IN ATBARA TEACHING HOSPITAL, SUDAN - Yasin Elmadhoun, Wadie Mohamed; Hussain, Omar (Gezira Journal of Health Sciences; Vol 7 No 1 (2011), 2011)
Background :  Providing data about the common causes of child death is essential to the development of national and local health policies for prevention and control of disease. Objective :  To determine the common causes of child mortality in Atbara Teaching Hospital, Sudan. Methods : In this retrospective study the records of children 0-15 years of age who died at Atbara Teaching Hospital within a 5 year period (Jan 2005 – Dec 2009) were reviewed for demographic data as well as the cause of death. Results : From a total of 14765 admissions to the pediatric ward in the five year period the total death was 344 (2.3%). Males were 215 (62.5%) and females 129 (37.5%). The under five were the majority ( 92.2%). Neonates constituted 25.8% of the total , older infants 42.9% and more than one year to five years 23.5%. The commonest causes of death were respiratory tract infections (18.2%) followed by malnutrition (16.6%), blood infections (15.4%), gastroenteritis and dehydration (15.4%), malaria (5.9%), scorpion sting (5.9%), heart failure (4.3%), meningitis (3.4%) and anemia (2.5%). At the bottom of the list were: tuberculosis (0.6%) and tetanus (0.3%). Conclusion : Causes of child mortality in Atbara are similar to those reported from other developing countries. Children under-five years of age are at the greatest risk of death from preventable and treatable diseases.